Organisational Change Experienced by HR Professionals : Case Nordea - Ekholm, Henrika (fi=Turun yliopisto|en=University of Turku|, 2017)
During the past decades, human resources managers have recognised the need for change, and the transition within the HR function combined with today’s highly competitive and rapidly changing business environment has led to changes in roles and responsibilities, as well as expectations and the positioning of HR professionals today. Although HR professionals most often see the concept of the change in HR as logical, many are discovering the difficulties associated to implementing extensive changes. However, the irony is that there is a demanding need for change management expertise from HR to support change in the business. Although HR professionals may often have experience in implementing change in the business, change can be just as challenging when it is targeted at the HR professionals themselves. In this study, HR professionals’ personal experiences are explored, shedding light on the factors that affect a change initiative in an HR department. The overall goal is to explore HR professionals as change targets and initiators taking into account how previous experiences with change might affect reactions and sensemaking towards change in the future. To ensure an understanding of the experiences related to the organisational change in question in this study, the research method used is a qualitative case study. The empiric study consists of seven semi-structured themed interviews with HR professionals from various teams and roles within the department. The research findings imply that in some cases too much is relied on the fact that HR professionals manage with less change management, because they should be professionals in change. In other words, change targeted at HR professionals themselves is no different from any other group of professionals. However, the results also indicate that previous experience with change can ease the change in the future, enhancing sensemaking of the change.